Absolute Authority Law Review Commission Supervision of Business Competition in Case of Tender “Build Operate Transfer” (Case Study : Commission Decision On Case No. 07/KPPU-L/2012, 16 / KPPU-L / 2014 and No. 01 / KPPU-L / 2015) - Karyono; Budianto, Azis (Greenation Publisher & Yayasan Global Resarch National, 2025)
The organization mainly in charge of carrying out Law No. 5 Year 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition (UULPM) is the Business Competition Supervisory Commission (KPPU). In UULPM if explored further turns can still cause a lot of problems, because the arrangements regarding the procedural law are not clear, giving rise to various interpretations and leads to the Commission’s outstanding (absolute) it is necessary to continue the assessment and monitoring so that implementation can be applied properly and effectively. The following factors contributed to the failure of the law's implementation: people who are unaware of law-abiding individuals and law enforcement authorities who enforce the law in an imprecise, ambiguous, and inconsistent manner, the facilities available to suport the implementation of the law is very less. The authority of the Commission are very extensive and outstanding (absolut) contained in UULPM beginning of investigation prosecution until the termination of the case so that the protection of businesses suspected of committing violations can hardly be separated from the law. This can be seen in the decision of cases auction “BUILD OPERATE TRANSFER” at the Commission that the writer used as a case study all unbeaten, even the power of the Commission were outstanding (absolute) can be seen in Article 47, Article 48 an Article 49 UULPM has the authority to bestows the criminal case to the Police.